The motifs of semai craft (anyaman) in Malaysia / Siti Nur Ayu Nuwin Johan Sutrio, Arba’iyah Ab. Aziz and Mohammad Kamal Abd Aziz - Johan Sutrio, Siti Nur Ayu Nuwin; Ab. Aziz, Arba’iyah; Abd Aziz, Mohammad Kamal (Universiti Teknologi MARA, 2020)
Anyaman is one of the most important crafts of Indigenous people. It is also the main craft and the economic source for this community. The pandanus and rattan are the most important material to make this craft. Anyaman is one of the acts of crossing some material especially pandanus and rattan until it is one object that can be used. It is because that craft is one of the identities of the Indigenous people especially Semai people. The Semai people is one of the biggest indigenous population in Malaysia. This research is focused on the motif of anyaman in the Semai community. This research took place in Pahang and Perak. The information was taken by using the qualitative method by observation, interview, and photograph. To get depth details of the research, Iconography theory by Erwin Panofsky was used. Despite that, there were ten motifs were retrieved from five weaving (anyaman) products in the Jahut tribe’s craft. Those motifs are divided into three categories which are flora, faunas, and still life. This research hopes to give a clear and wider understanding to the reader especially in the context of art, culture, and heritage as well.